Analyzing Students’ Feedback on Pre-Service Teachers’ Teaching Strategies in Eenglish as a Foreign Language Classrooms - Eca Ayu Nurfadhilah; Novi Rahmania Aquariza; Edi Pujo Basuki; Nailul Authar (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The effectiveness of teaching strategies plays a crucial role in facilitating students’ learning experiences, particularly in English as a Foreign Language (EFL) classrooms where exposure to English is often limited. As part of their professional preparation, pre-service teachers are expected to implement instructional strategies that support students’ engagement and comprehension during teaching practicum programs. However, previous studies have predominantly focused on quantitative evaluations of teaching performance, providing limited insight into students’ detailed perspectives regarding the teaching strategies employed by pre-service teachers. Therefore, this study aimed to analyze students’ feedback on pre-service teachers’ teaching strategies in EFL classrooms. This study employed a qualitative descriptive design involving senior high school students who attended EFL classes taught by pre-service teachers during their teaching practicum. Participants were selected through purposive sampling. Data were collected through open-ended questionnaires and semi-structured interviews and analyzed using thematic analysis. The findings revealed four major themes influencing students’ perceptions: clarity of material delivery, teacher–student interaction, student engagement techniques, and the use of varied teaching methods. Students generally responded positively to instructional strategies that encouraged active participation, interactive communication, and meaningful learning experiences. Activities such as group discussions, games, and question-and-answer sessions were perceived as effective in enhancing motivation and classroom engagement. Nevertheless, some students reported difficulties in understanding lessons when complex English expressions were used. This study contributes to the field of EFL pedagogy and teacher education by highlighting the importance of student feedback as a valuable source for evaluating and improving teaching practices.